ASSESSMENTS OF YIELD LOSS OF GROUNDNUT DUE TO STEM AND POD ROT - K. B. RAKHOLIYA (The Bioscan, 2019)
Field experiments were conducted during kharif-2007 and kharif-2008 at farm of department of plant pathology, college of agriculture, Junagadh Agricultural University, Junagadh for assessment of yield losses due to stem and pod rot of groundnut. Susceptible variety of groundnut GG-20 was selected for assessment of yield loss. Minimum stem and pod rot disease incidence and maximum pod yield (2093kg/ha) was recorded in seed treatment with vitavax power 3g/kg seeds + furrow application of T. harzianum @1.5 kg/ha mixed in 300kg fym/ha at the time of sowing + three sprays of hexaconazole (0.005%) at 35, 55 and 75 days after sowing in protected plots. The yield loss was 856 kg/ha recorded in unprotected plot. The pod yield loss 40.89 % was recorded in groundnut due to stem and pod disease in unprotected plot.